2010
DOI: 10.5012/bkcs.2010.31.11.3103
|View full text |Cite
|
Sign up to set email alerts
|

Application of Polyaniline to an Enzyme-Amplified Electrochemical Immunosensor as an Electroactive Report Molecule

Abstract: Conducting polymers (CPs) are widely used as matrixes for the entrapment of enzymes in analytical chemistry and biosensing devices. However, enzyme-catalyzed polymerization of CPs is rarely used for immunosensing due to the difficulties involved in the quantitative analysis of colloidal CPs in solution phase. In this study, an enzyme-amplified electrocatalytic immunosensor employing a CP as a redox marker has been developed. A polyanionic polymer matrix, α-amino-ω-thiol terminated poly(acrylic acid), was emplo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
8
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 29 publications
(27 reference statements)
0
8
0
Order By: Relevance
“…It is, apparently, suggested that an advanced polymer layering process such as automated ink-jet printings could improve the reproducibility of chips. These values, however, are in the range of generally accepted values reported for the IgG quantification by using electrochemical sensor systems 27 and ELISA.…”
mentioning
confidence: 47%
“…It is, apparently, suggested that an advanced polymer layering process such as automated ink-jet printings could improve the reproducibility of chips. These values, however, are in the range of generally accepted values reported for the IgG quantification by using electrochemical sensor systems 27 and ELISA.…”
mentioning
confidence: 47%
“…16,17 In addition, PANI is a leading material in the study of conducting polymers as a result of its ease of modication, processing, adaptability and stability. 18,19 It is these benets that inuenced their choice for this study.…”
Section: Introductionmentioning
confidence: 99%
“…Catalytic precipitation of a redox-active film on an electrode, and subsequent electrochemical oxidation or reduction of the film, have been widely used in electrochemical biosensors. To obtain sensitive detection, the catalytic precipitation should be very fast and should not occur in the absence of a catalyst, and the precipitate film should be insoluble in an aqueous electrolyte solution, tightly bound to a sensing electrode, and highly redox-active and noninsulating within an electrochemical potential window. Although a thicker precipitate film allows for a higher electrochemical signal, many thick precipitate films behave like insulators .…”
mentioning
confidence: 99%
“…However, this method has some limitations: Ag deposition cannot be performed in a solution containing Cl – because of the formation of AgCl precipitate, and nonspecific Ag deposition can occur even in the absence of catalyst. Enzymatic deposition of a conducting polymer film and subsequent electrochemical oxidation of the film have also been developed to obtain specific precipitation and high electrochemical signal. , However, the enzymatic polymerization is too slow to obtain a high electrochemical signal, and it is difficult to obtain a film tightly bound to an electrode as polymerized oligomers with low molecular weights are soluble in a solution and diffuse away from the electrode.…”
mentioning
confidence: 99%
See 1 more Smart Citation